Rapid and efficient method for removal of basic dyes from wastewater with bis(trifluoromethanesulfonyl)imide anion. (16th October 2018) - Kim, Jeong Yun; Woo, Sung Wun; Hwang, Tae Gyu; Kim, Hong Mo; Sakong, Chun; Choi, Jun; Lee, Woosung; Kim, Jae Pil
Abstract : A novel and simple method for the removal of the basic dyes from wastewater is suggested in this paper. A bulky and symmetric counteranion is introduced to basic dyes for forming precipitates upon counteranion substitution. The precipitates are separated from the water by filtration. The dye removal method is applied to eight commercial basic dyes and the dye removal efficiency is assessed based on absorbance and transmittance data. Half of the basic dyes used require less than 5 min, and the other half is removed with 98% efficiencies within 30 min. In comparison with the previously reported methods for this concern, the dye removal method suggested in this study is quick, easy and involves a little energy consumption. Moreover, this method exhibits superior dye removal efficiency and can be applied to all basic dyes regardless of their structures or other properties. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S146–S156, 2019